شراء الأصوات الانتخابية في إندونيسيا : دراسة فقهية تحليلية - مخلص، زيني (Kulliyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2015)
This research revolves on the study of the vote buying in general elections in some democracies, with special focus on Indonesia. Likewise, the researcher set out to analyze the causes of this phenomenon and to uncover its relationship with bribery, perjury and breach of trust. He also attempted to elucidate the Sharia rule concerning this practice based on a discussion of the different views of Muslim jurists in order to suggest the ways and means necessary to deal with this practice so as to curb it and put an end to it. The researcher has employed the analytical method to shed light on the different aspects of vote buying and show its different procedures and forms. He also used the inductive method for surveying the relevant Qur'anic texts and Prophetic traditions as well as learning about the jurists' views concerning this phenomenon in order to critically assess and them and contrast them to each other and give preponderance to that which adequate by virtue of the strength of its evidence and its suitability to the needs of modern life. The researcher has arrived at a number of greatly significant findings. The first and most important finding is that the phenomenon of vote buying is a major cause of political and administrative corruption in Indonesia as it is the main incubator breeding corrupt leaders, a fact that affects all state institutions especially in the economic sector. Secondly, the study has shown that the phenomenon of vote buying is so widely and profoundly spread in the life of the Indonesian society that practicing is looked as if it were an established custom, which makes combating it a difficult task. Thirdly, it has been shown that there are two main positions among Indonesian jurists and Shari'ah scholars regarding this practice: those who forbid it categorically and those who sanction it. Finally, based on investigation and weighing of evidences and consequences it has been demonstrated that vote buying in all its forms must be forbidden due the fact that it is an illegitimate way of accessing to authority and due to the corruption it incurs in the society's public and private life.